Using fracture-based continuum modeling of coupled geomechanical-hydrological processes for numerical simulation of hydraulic fracturing - Goodluck I. Ofoegbu (Journal of Rock Mechanics and Geotechnical Engineering, 2024)
This paper describes numerical simulation of hydraulic fracturing using fracture-based continuum modeling (FBCM) of coupled geomechanical-hydrological processes to evaluate a technique for high-density fracturing and fracture caging. The simulations are innovative because of modeling discrete fractures explicitly in continuum analysis. A key advantage of FBCM is that fracture initiation and propagation are modeled explicitly without changing the domain grid (i.e. no re-meshing). Further, multiple realizations of a preexisting fracture distribution can be analyzed using the same domain grid. The simulated hydraulic fracturing technique consists of pressurizing multiple wells simultaneously: initially without permeating fluids into the rock, to seed fractures uniformly and at high density in the wall rock of the wells; followed by fluid injection to propagate the seeded fracture density hydraulically. FBCM combines the ease of continuum modeling with the potential accuracy of modeling discrete fractures and fracturing explicitly. Fractures are modeled as piecewise planar based on intersections with domain elements; fracture geometry stored as continuum properties is used to calculate parameters needed to model individual fractures; and rock behavior is modeled through tensorial aggregation of the behavior of discrete fractures and unfractured rock. Simulations are presented for previously unfractured rock and for rock with preexisting fractures of horizontal, shallow-dipping, steeply dipping, or vertical orientation. Simulations of a single-well model are used to determine the pattern and spacing for a multiple-well design. The results illustrate high-density fracturing and fracture caging through simultaneous fluid injection in multiple wells: for previously unfractured rock or rock with preexisting shallow-dipping or horizontal fractures, and in situ vertical compressive stress greater than horizontal. If preexisting fractures are steeply dipping or vertical, and considering the same in situ stress condition, well pressurization without fluid permeation appears to be the only practical way to induce new fractures and contain fracturing within the target domain.